Legitimizing Religious Court Authority: Strengthening Public Confidence in Sharia Economic Dispute Resolution in Indonesia - Asyiqin, Istianah Zainal (Universitas Muhammadiyah Yogyakarta, 2026)
The Religious Court in Indonesia has formal authority to resolve Sharia economic disputes. However, in practice, its role in this field remains limited, as the public still largely associates the institution with family law matters such as divorce, inheritance, child custody, wills, and grants. This condition reflects a broader issue of public trust and awareness regarding the Religious Court’s capacity to handle Sharia economic cases. This study examines the factors that contribute to this limited trust and how they affect the use of the Religious Court as a forum for economic dispute resolution. Using normative legal research, this study analyzes statutory regulations, Religious Court decisions, legal doctrines, academic literature, and relevant institutional reports concerning Sharia economic dispute resolution in Indonesia. The findings show that public trust is weakened by three main factors: historical and regulatory limitations, inadequate court facilities to meet business needs for efficient dispute resolution, and low legal literacy among Sharia economic actors. Strengthening the Religious Court, therefore, requires regulatory reform, institutional improvement, better infrastructure, and sustained legal education. This study also highlights the importance of further research on public perceptions of the Religious Court.